If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4u + -6) + -1u = 0 Reorder the terms: -1(-6 + 4u) + -1u = 0 (-6 * -1 + 4u * -1) + -1u = 0 (6 + -4u) + -1u = 0 Combine like terms: -4u + -1u = -5u 6 + -5u = 0 Solving 6 + -5u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5u = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5u = 0 + -6 -5u = 0 + -6 Combine like terms: 0 + -6 = -6 -5u = -6 Divide each side by '-5'. u = 1.2 Simplifying u = 1.2
| 8x-3(3x+2)= | | 2x^2+22=0 | | 7(x-7)+16= | | 92=6(x-70)+50 | | 2x^4-x^3-x^2=0 | | x^2+y^2-4x-6y+4=0 | | 2y-2=6y+2 | | -2(-y-2)-x= | | 6x^2+7x-3=y | | .2+.2x=.4 | | 12x^2+82x-14=0 | | 3(1+d)+-5=3d+-2 | | 3x^2-35x-5=0 | | 6x-1=6x+12 | | 2yw+4y-yw-3y= | | -4w+1+w-6= | | kv-kv^2=q | | (6y+4)-(2+5y)=8 | | -20+X=51 | | 12x+3x-12=0 | | 3x^2-42x+147+9=0 | | 16m^2-8m-3=0 | | 5.9+x=4.1 | | 10=27-2(-3-2w) | | A^5+4-6a^3=0 | | 5z+5h+n=q | | x^3-3x^2-2x+6=0 | | A^5+4+2a=0 | | 11=29-8(-1-5w) | | 11x-32=7x+4 | | 6y-(y-8)=-20 | | 246(98x)=x |